Bioformulation Development of Bacillus velezensis Strain N1 to Control Rice Bacterial Leaf Blight - Sawatphanit, Nattina; Sutthisa, Waraporn; Kumlung, Tantima (Trends in Sciences, 2022)
Bacterial leaf blight is a serious disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). The objective of this study was to develop a bioformulation of Bacillus velezensis strain N1 by using microencapsulation techniques through spray drying and to then evaluate its performance in controlling rice bacterial leaf blight under greenhouse conditions. Three formulations with a different main carrier were studied and the viability after spray drying, moisture content, characteristic of formulation powder under scanning electron microscope and storage stability were examined. The results showed that formulation 3 (10 % skimmed milk, 20 % maltodextrin, 0.06 % sodium alginate and 5 % tapioca starch) had the highest antagonistic bacterial viability after spray drying of 1.24×107 CFU/g. Formulation 2 had the highest antagonistic bacterial viability of 1.44×106 CFU/g and had the lowest viability reduction of 0.61 Log CFU/g after storage at room temperature for 3 months. Moisture content of each formulation was less than 4 %. Among the 3 formulations of strain N1 bacteria against Xoo, formula 2 was able to control rice bacterial blight disease with the highest disease reduction index (45.87 %). All the results indicated that Bacillus velezensis strain N1 can be an effective antagonist and could potentially be used to develop a more successful bioformulation against rice bacterial leaf blight. GRAPHICAL ABSTRACT